A Disintegrin and Metalloproteinase Domain 17 Regulates Colorectal Cancer Stem Cells and Chemosensitivity Via Notch1 Signaling. (7th January 2016) - Wang, Rui; Ye, Xiangcang; Bhattacharya, Rajat; Boulbes, Delphine R.; Fan, Fan; Xia, Ling; Ellis, Lee M.
Abstract: : Evidence is accumulating for the role of cancer stem cells (CSCs) in mediating chemoresistance in patients with metastatic colorectal cancer (mCRC). A disintegrin and metalloproteinase domain 17 (ADAM17; also known as tumor necrosis factor-α-converting enzyme [TACE]) was shown to be overexpressed and to mediate cell proliferation and chemoresistance in CRC cells. However, its role in mediating the CSC phenotype in CRC has not been well-characterized. The objective of the present study was to determine whether ADAM17 regulates the CSC phenotype in CRC and to elucidate the downstream signaling mechanism that mediates cancer stemness. We treated established CRC cell lines and a newly established human CRC cell line HCP-1 with ADAM17-specific small interfering RNA (siRNA) or the synthetic peptide inhibitor TAPI-2. The effects of ADAM17 inhibition on the CSC phenotype and chemosensitivity to 5-fluorouracil (5-FU) in CRC cells were examined. siRNA knockdown and TAPI-2 decreased the protein levels of cleaved Notch1 (Notch1 intracellular domain) and HES-1 in CRC cells. A decrease in the CSC phenotype was determined by sphere formation and ALDEFLUOR assays. Moreover, TAPI-2 sensitized CRC cells to 5-FU by decreasing cell viability and the median lethal dose of 5-FU and increasing apoptosis. We also showed the cleavage and release of soluble Jagged-1 and -2 by ADAM17 in CRC cells. Our studies have elucidated a role of ADAM17 in regulating the CSC phenotype and chemoresistance in CRC cells. The use of drugs that inhibit ADAM17 activity might increase the therapeutic benefit to patients with mCRC and, potentially, those with other solid malignancies. Significance: The present study has demonstrated the role of A disintegrin and metalloproteinase domain 17 (ADAM17) in regulating cancer stemness and chemosensitivity in colorectal cancer (CRC) cells. In addition, a previously unknown cleavage of the Notch ligands Jagged-1 and -2 by ADAM17 in CRC cells is reported. These findings will have an impact on future studies of the regulation of cancer stem cells in CRC and, potentially, other cancer types. Abstract : The objective was to determine whether A disintegrin and metalloproteinase domain 17 (ADAM17) regulates the cancer stem cell (CSC) phenotype in colorectal cancer (CRC) and elucidate the downstream signaling mechanism mediating cancer stem-ness. The results showed that ADAM17 has a role in regulating the CSC phenotype and chemoresistance in CRC cells. Drugs that inhibit ADAM17 activity might increase the therapeutic benefit to metastatic CRC and, potentially, other solid malignancies.